Economic crisis and female entrepreneurship: Evidence from countries in Eastern Europe and Central Asia - Saumik Paul; Vengadeshvaran Sarma (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2013)
Building on the theory of necessity entrepreneurship, we test whether female entrepreneurship was a part of the household coping mechanism facing the recent global crisis across 30 transition countries centered in Eastern Europe and Central Asia. The identification strategy relies on the self-reported crisis victimization indicators at the household level. Main findings indicate that female members from crisis-affected households are more willing to become entrepreneurs and have initiated firms at a significantly higher rate since 2007. The estimated outcomes are particularly critical for male headed households with propensity score matching and doubly robust tests supporting the main findings. We also find that prior entrepreneurial activity at the household level, acts as a catalyst for such female necessity entrepreneurship. Overall, the findings suggest that crisis perhaps worked as a contextual factor contributing to the creation of necessary entrepreneurship among women.
Keywords: L26; D13; J16; 330; Female Entrepreneurship; Economic Crisis; Eastern Europe and Central Asia